Protective role of intraperitoneally administrated vitamin E and selenium on the levels of total lipid, total cholesterol, and fatty acid composition of muscle and liver tissues in rats - Yilmaz, O; Celik, S; Cay, M; Naziroglu, M (Wiley, 1997)
The aim of this work was to determine the protective effects of intraperitoneally administrated vitamin E and Se on total lipid, total cholesterol, and fatty acid composition of rat liver and muscle tissues. Total lipid content of muscle tissue in Se and combination groups decreased as compared to the control group. However, the level of total lipid in the liver tissues was seen to decrease only in the combination group (P < 0.05). While the amount of total cholesterol in liver tissue was lower (P < 0.05) in the vitamin E and combination groups, the amount of total cholesterol in muscle tissue decreased (P < 0.05) in the combination group. The amount of linoleic acid in muscle tissue slightly decreased (P < 0.05), whereas the eicosenoic and eicosatrienoic acid amounts significantly increased (P < 0.01, P < 0.001) in the vitamin E group as compared to the control group. The amounts of most fatty acid decreased (P < 0.05) in the combination group. The proportions of eicosenoic, eicosatrienoic, and total polyunsaturated fatty acid (PUFA) within the total fatty acid were higher (P < 0.05) in vitamin E group, whereas these fatty acids proportions were lower (P < 0.05) in the Se group. Although the proportions of palmitic, linolenic, and total saturated fatty acids were low (P < 0.05), oleic and total unsaturated fatty acid proportions were higher (P < 0.05) in the combination group than in the control group. The amount of palmitic acid and total saturated fatty acid in liver tissue decreased (P < 0.01 and P < 0.05, respectively) in the Vitamin E and combination groups. However, the amount of linoleic acid only decreased (P < 0.05) in the combination group. The amount of PUFA was slightly higher (P < 0.05) in Vitamin E. The proportions of stearic acid and linoleic acid decreased (P < 0.05) both in the Se and combination groups. However, the proportions of eicosatrienoic, omega 6, and PUFA were slightly higher (P < 0.05) in the vitamin E group, but total saturated fatty acid proportion significantly decreased (P < 0.01) in both the vitamin E and combination groups. In conclusion, the level of total lipid and cholesterol in muscle and liver tissues were reduced by administrating vitamin E and Se together. Additionally, the fatty acid synthesis in the muscle and liver tissues was decreased by this process. However, it was observed that the protective effect of intraperitoneally administrated vitamin E was higher than Se on fatty acid composition in muscle and river tissues. (C) 1997 Wiley-Liss, Inc.
Keywords: intraperitoneally administrated; vitamin E; Se; liver; muscle; fatty acids; rats